Hommage à Annette Karmiloff-Smith / Homenaje a Annette Karmiloff-Smith. Issue 1 (2nd January 2018) - Berman, Ruth A.
Abstract: This brief homage touches on a few of Annette Karmiloff-Smith's outstanding scholarly contributions in the cognitive sciences, her unique personal attributes and the impact her work and life have had on the author and on many others in the cognitive sciences since she completed her doctoral studies at the University of Geneva in the 1970s.